Virtual libraries in the new metaverse: An exploratory study on community libraries in Meta Horizon Worlds - Hollister, Jonathan M. (International Journal of Knowledge Content Development & Technology, 2025)
To explore the presence and status of libraries in the metaverse, focusing on the social virtual reality (VR) platform Meta Horizon Worlds. This study employs unobtrusive observation by collecting data within public VR library worlds and from their listings on the platform. Data was interpreted using qualitative data analysis and open coding. Forty-four virtual libraries were identified in Meta Horizon Worlds, serving as art and asset libraries, community libraries, personal libraries, or other library-themed spaces for games and socialization. Few virtual libraries seem to be associated with “real-world” libraries, suggesting that there may be opportunities for growth if Meta Horizon Worlds remains a stable part of the metaverse. This study appears to be among the first to explore virtual libraries in Meta Horizon Worlds in situ via VR-based data collection.